2015
DOI: 10.32007/jfacmedbagdad.571308
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight loss achieved through gastric sleeve surgery with circulating level of ghrelin hormone in obese Iraqi subjects.

Abstract: Back ground: The epidemic of obesity is a major health problem in the developed world with a great influence on morbidity and mortality.The aim of study: to evaluate serum ghrelin levels achieved through LSG and on insulin resistance and the serial changes of insulin concentration in obese patients following gastric sleeve.Patients and methods: twenty four patients underwent LSG with 25 controls were selected. Body mass index (BMI), waist circumference (WC), lipid profile, fasting blood sugar (FBS), glycated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…While Marzullo et al mentioned that total ghrelin and plasma active ghrelin were significantly low in obese when compared with lean subjects [23] Ghani et al (2015) found that circulating ghrelin levels are decreased in human obesity and plasma ghrelin level showing a negative correlation with BMI [24].…”
Section: Resultsmentioning
confidence: 99%
“…While Marzullo et al mentioned that total ghrelin and plasma active ghrelin were significantly low in obese when compared with lean subjects [23] Ghani et al (2015) found that circulating ghrelin levels are decreased in human obesity and plasma ghrelin level showing a negative correlation with BMI [24].…”
Section: Resultsmentioning
confidence: 99%